﻿Three novel species of Distoseptispora (Distoseptisporaceae) isolated from bamboo in Jiangxi Province, China - Zhi-Jun Zhai; Jun-Qing Yan; Wei-Wu Li; Yang Gao; Hai-Jing Hu; Jian-Ping Zhou; Hai-Yan Song; Dian-Ming Hu (MycoKeys, 2022)
Decaying bamboo in freshwater is a unique eco-environment for fungi. Three new Distoseptispora (Distoseptisporaceae) species, D. meilingensis, D. yongxiuensis and D. yunjushanensis from submerged decaying bamboo culms in Jiangxi Province, China, were discovered, based on phylogenetic analyses and morphological characters. The combined data of ITS-LSU-SSU-Tef1 sequences were used to infer the phylogenetic relationship between D. meilingensis, D. yongxiuensis, D. yunjushanensis and related species. Both molecular analyses and morphological data supported D. meilingensis, D. yongxiuensis and D. yunjushanensis as three independent taxa.